Peran Zakat, Infaq dan Sedekah dalam Meningkatkan Kesejahteraan Difabel Cerebral Palsy melalui Program Jombang Sehat: Studi pada BAZNAS Jombang - Yundha, Ayus Rahma; Hanifah, Luluk (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
Cerebral palsy is a child with special needs where cerebral paralysis occurs, which causes disturbances in the development and growth processes both physically and emotionally. People with cerebral palsy require special attention and regular care, which requires assistance. So, based on this problem, researchers want to examine how much ZIS funds are utilized for people with cerebral palsy, specifically in the Jombang Regency area. The type of research used is a descriptive qualitative approach. Descriptive qualitative research is a type of research in which a researcher investigates events and phenomena in the lives of individuals and asks a person or group of individuals to talk about their lives. The information obtained by the researcher is retold. by researchers in descriptive chronology. In this research, the data used is qualitative data sourced from primary data and secondary data. Primary data is collected through interviews and documents, and secondary data is analyzed through financial reports and annual magazines at BAZNAS Jombang Regency. This research shows that the distribution of Zakat, Infaq, and Alms at BAZNAS Jombang Regency has a role in improving the welfare of mustahiks who suffer from cerebral palsy. This role includes providing milk or nutritional assistance, vitamins, snacks, leg support, routine therapy every week, and helping the mustahik's daily economy.